Forest Soil Organic Carbon Stocks of Tessala Mount in North-West Algeria-Preliminary Estimates - Merabtene, Mohammed Djemel; Faraoun, Fatiha; Mlih, Rawan; Djellouli, Riad; Latreche, Ali; Bol, Roland (Frontiers in Environmental Science, 2021)
Mountainous forests in Algeria are severely affected by climate change. The degradation is exacerbated by overgrazing, deforestation, and poor land management linked to the harsh topographical conditions of the mountain agrosystem. These conditions have influenced the turnover of the soil organic matter and thus the SOC stocks storage. This study aims to investigate the average of organic carbon stored in forest soils of Tessala Mount in Algeria and to examine the influence of different plant formations alongside with geographical characteristics and soil physicochemical properties on the amount of carbon stored in the soil. We estimated the critical threshold, the saturation point, and the organic carbon deficit of soils. The correlation between geographical characteristics and soil physicochemical properties and soil organic carbon stocks was determined using principal component analysis and other statistical tools. The results of the study show that the organic carbon stock in soils of Tessala Mount area has an average value of 77.4 t ha−1. The maximum average of SOC stocks (121 t ha−1) of 0–30 cm depth was noted under dense matorral of green and kermes oak followed by sparse garrigue with a value of 112 t ha−1. The soil organic carbon stock in Tessala region was positively correlated with coarse silt, elevation, and northern exposure, but negatively with calcium carbonates contents. The current carbon contents of Tessala topsoil are 22 g C kg−1 which is very low and closer to the critical threshold (11 g C kg−1) whose estimate was based on their clay and silt content. The estimated maximum storage capacity is 160 g C kg−1. The preliminary estimate of the forest soils organic carbon stock of Tessala Mount under current natural conditions indicates an alarming situation with a low rate close to the critical threshold, thus exposing this area to further and stronger degradation.